CITY’S MARGINS AND URBAN POLICIES. THE CASE OF CHERARBA IN THE OUTSKIRTS OF ALGIERS - Nora Semmoud; Florence Troin (Bollettino della Società Geografica Italiana)
Moving from the case of Cherarba, a popular district located in the eastern suburbs of Algiers, the paper focuses on the controversial relations between public policies and spaces of informality within the city. Urban margins are here conceived as direct expression of the social logics of contemporary urban policies. From the one side, the paper analyses the social impacts of neoliberal policies in Algiers, stressing the socio-spatial inequalities deriving from the concentration of public funds on real estate developments, to the detriment of marginal suburbs. From the other side, the work highlights how the social practices and know-hows of Cherarba’s residents may be used as a mean for the socio-spatial integration of the district within the city.